Acoustophoretic particle manipulation in hybrid solid/gel resonators - Luzuriaga, Jon; Carreras, Pilar; Candil, Manuel; Bazou, Despina; González, Itziar (Frontiers in Physics, 2022)
This study presents a proof of concept to demonstrate the ability of ultrasounds to perform acoustophoretic processes in hybrid millifluidic resonators that include channels laterally embedded in extremely soft media with physical properties close to those of liquids. In our experiments, particles are driven by acoustic radiation forces toward hydrodynamic/acoustic equilibrium positions in a similar way to that produced in conventional microfluidic resonators with solid structures; 20 um-sized polystyrene beads immersed in deionized water flow channelized throughout an aqueous-based gel between an inlet and outlet in a resonant chamber while being exposed to ultrasounds at a frequency of 1.54 MHz. The liquid channel formed presents irregular walls and variable geometry defined by the sample injection pressure. Particles collect rapidly along a central line equidistant from the walls, regardless of whether they are parallel or not, as observed for different channel geometries and cross-sectional dimensions. Only when the flow stops, the particles collect in acoustic pressure nodes established with the 2D spatial distribution. These results break the paradigm of solid structures as essential physical elements to support acoustophoresis, demonstrating the ability to produce these processes in media without a consolidated structure. It opens a door to bioprinting applications.